(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Based on previous research, this paper proposesarevolutionary hypothesis about the essence of electrons. The studyfirst draws on the innovative description of the wave-particle dualityof photons in “Hypothesis on the Spatial Motion Mode of Photons”, combines the theoretical derivation of the possibility of the existenceof ether space in “Several Conjectures on the Existence of Ether”, and the breakthrough idea of the electron structure model, andcreatively puts forward the “Hypothesis on the Ether Space Structureof Electrons”. This hypothesis challenges the traditional viewintheories that regards electrons as point particles, and argues that electrons are essentially entities with a wave-particle dualityetherspace structure. This study systematically elaborates on the uniqueether vortex structure and quantum dynamic behavior of electrons, constructs a brand-new theoretical framework to explainthewave-particle duality of electrons, and provides newunderstandingthe theoretical principles of basic particles such as electrons. Thistheoretical innovation not only helps to deepen the understandingofthe essence of electrons, but may also open up newresearchpathsfor unifying quantum mechanics and classical physics.